Omalizumab as a Provoking Factor for Venous Thromboembolism - Crhistian-Mario Oblitas; Francisco Galeano-Valle; Laura Vela-De La Cruz; Jorge Del Toro-Cervera; Pablo Demelo-Rodríguez (AboutScience Srl, 2019)
A 43-year-old man with a history of severe extrinsic allergic asthma treated with once-monthly omalizumab (600 mg) for the last 15 months. He presented to the emergency room with a 2-week history of right lower limb pain and chest pleuritic pain. Computed tomography pulmonary angiography showed bilateral pulmonary embolism with right-sided pulmonary infarction and ultrasound of right lower limb confirmed distal deep vein thrombosis. No other known risk factors were identified. Treatment with omalizumab was stopped during hospitalization. The Naranjo Adverse Drug Reaction (ADR) Probability Scale classifies this as a probable ADR (score of 6). Omalizumab is a humanized monoclonal anti-IgE antibody indicated for the treatment of persistent moderate-to-severe asthma and certain chronic refractory urticaria. The EXCELS study (The Epidemiologic Study of Xolair (omalizumab): Evaluating Clinical Effectiveness and Long-term Safety in Patients with Moderate-to-Severe Asthma), a postmarketing observational cohort study to assess clinical safety profile of omalizumab, showed a significant increase in venous thromboembolism. In conclusion, omalizumab has been associated with arterial and venous thromboembolic events, although the evidence is not definitive.